2006
DOI: 10.1097/01.ede.0000239581.76793.ae
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Use of Selective Serotonin Reuptake Inhibitors and Risk of Congenital Malformations

Abstract: We found an increased risk of congenital malformations after exposure to SSRIs in early pregnancy. It is unclear whether the effects were causal or due to factors related to the underlying disease. There was no evidence that the association was specific to particular malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(135 citation statements)
references
References 14 publications
2
124
3
3
Order By: Relevance
“…4 In 2005, based on early results of two epidemiologic studies, the US Food and Drug Administration (FDA) warned healthcare professionals that early prenatal exposure to paroxetine may increase the risk of congenital cardiac malformations and reclassified it to pregnancy category D. 5 Most malformations in the early reports leading to the FDA warning were septal defects. Since then, several studies have evaluated the teratogenicity of SSRIs and other antidepressants [6][7][8][9][10][11][12][13][14][15][16][17][18][19] , but considerable controversy remains as to whether this is a "serious concern or much ado about little" as noted in an editorial published with two of the reports. 13,1420 Existing studies have reported different associations, often in the context of multiple comparisons.…”
Section: Conclusion-resultsmentioning
confidence: 99%
“…4 In 2005, based on early results of two epidemiologic studies, the US Food and Drug Administration (FDA) warned healthcare professionals that early prenatal exposure to paroxetine may increase the risk of congenital cardiac malformations and reclassified it to pregnancy category D. 5 Most malformations in the early reports leading to the FDA warning were septal defects. Since then, several studies have evaluated the teratogenicity of SSRIs and other antidepressants [6][7][8][9][10][11][12][13][14][15][16][17][18][19] , but considerable controversy remains as to whether this is a "serious concern or much ado about little" as noted in an editorial published with two of the reports. 13,1420 Existing studies have reported different associations, often in the context of multiple comparisons.…”
Section: Conclusion-resultsmentioning
confidence: 99%
“…At present, a much used methodology is based on linkage between national or regional registers of prescriptions with registers of delivery outcomes. Such studies of antidepressants have been made for instance in Canada [5,6], Finland [7], and Denmark [8,9]. Timing of drug use during pregnancy is then made from the date of filling the prescription related to the week of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Although these disorders are generally associated to genetic abnormalities, they can also be induced by prenatal exposure to teratogens. SSRIs represent a class of commonly used antidepressants in pregnant and lactating women and several epidemiological investigations report long-lasting molecular, physiological and behavioral changes in offspring prenatally exposed B C A Serotonin 2B receptor developmental role 713 2005 and 2006, stating that the use of SSRIs in pregnancy was associated with increased birth defects (Chambers et al, 2006, Wogelius et al, 2006. Prenatal exposure to SSRIs also impacts fetal brain development that may have long-term mental health implications (Hanley et al, 2013).…”
Section: Discussionmentioning
confidence: 99%